Death Penalty for Corruption Crimes Reviewed From a Human Rights Perspective - Sujono, Sujono; Dirgantini, Marissa Kemala; Atmoko, Dwi (Action Research Literate, 2024)
Prevention & eradication of criminal acts of corruption in Indonesia has been very intensively implemented because corruption in Indonesia is now so rampant, acute, and systemic. The existence of firm and harsh criminal sanctions has a very important role in the process of eradicating corruption. In Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes or what is called the PTPK Law, there is a juridical space that can be used to impose death penalty sanctions on perpetrators of criminal acts of corruption, namely in Article 2 paragraph (2) The PTPK Law stipulates that if the criminal act of corruption as intended in paragraph (1) is committed under certain circumstances, the death penalty can be imposed." However, until now in its implementation, there has never been a single court decision in Indonesia that dared to use this article. Apart from that, imposing the death penalty sanction is not easy because there is still debate because not all people agree with this heaviest sanction, they argue that imposing the death penalty sanction is considered to violate human rights. The issue of protecting human rights, especially the right to life, has so far been the main reason for imposing the death penalty for perpetrators of criminal acts of corruption. Furthermore, those who oppose the imposition of death penalty sanctions feel that the right to life is an absolute right that cannot be revoked by anyone except God, and this right is protected by the 1945 Constitution, Article 28 I paragraph (1). Given this, the enforcement of death penalty sanctions against perpetrators of criminal acts of corruption will of course become an obstacle in its enforcement in the future